Protection of Azerbaijani Language in e-government platform - Alguliyev, Rasim; Yusifov, Farhad; Gurbanova, Afruz (e-Journal of Linguistics; Vol 15 No 2 (2021): e-jl July, 2021)
The protection of language diversity has become one of the topical issues in the rapidly globalizing modern world influenced by information technology. The article studies the protection of Azerbaijani language in e-government. The approaches to the impacts of globalization on lingua-cultural space and linguistic processes are explored. The protection of linguistic diversity and the application opportunities of linguistic technologies in e-government are analyzed. The approaches to the protection of Azerbaijani language in e-Azerbaijan segment of the global information space are provided. A conceptual model that provides effective mechanisms for the application of linguistic technologies is proposed. In general, there are various ideas and approaches related to language protection on the Internet. There are many factors endangering language in the globalization process, and it is not possible to maintain the language at the expense of controlling each of these factors. In this regard, the Internet can also be used to raise awareness about the language loss and language protection. The application of cloud-based linguistic technologies enables the provision of different services over the Internet (translation, cataloging, data storage, availability etc.). They can also be used to preserve the integrity of spoken language. Furthermore, many of these technologies used for sound and speech recognition can be applied to protect spoken languages. The use of linguistic technologies in e-Azerbaijan segment of the unique information space will contribute to the protection and development of Azerbaijani language by providing variety of e-services.